Pengaturan diri dan tingkatan semester terhadap kecanduan social media pada mahasiswa perempuan di perguruan tinggi Islam - Paulina, Melisa; Rahmi Qadriyah, Siti; Nurjamilah; Eva Sri Wahyuni; Rahman Saktiawan R Kalake (Program Studi Tasawuf dan Psikoterapi, 2024)
The impact of social media on female depends largely on how and to what extent social media is used. Female on social media face unique challenges and opportunities. Meanwhile, social media can be a source of pressure in response to excessive communication and information. So this research aims to see the influence of Self Regulation and Semester Level on social media addiction in female students at Islamic universities. This research uses a quantitative approach with a cross sectional design. The sampling technique used is a purposive sampling technique with certain considerations or criteria. The sample consisted of 357 female students. Results Study find the F test is 0.225 with a sig of 0.799 (sig < 0.05) meaning that there is no significant influence between self-regulation variables and semester level on Islamic female students' social media addiction. The influence of the R Square proportion on self-regulation variables and semester level together they have an influence on social media addiction of 1% while the remaining 99 % is influenced by other variables outside the research. In detail, for the self-regulation variable the regression coefficient value is -0. 28 and a significance value of 6.01 (sig > 0.05). For semester level variables, the regression coefficient value is 0.102 and the significance value is 0.697 (sig > 0.05).